Virgin coconut oil: extraction: physicochemical properties, biological activities and its authentication analysis - ., Abdul Rohman; ., Irnawati; Erwanto, Yuny; Rafi, Muhamad; Ahmad Fadzillah, Nurrulhidayah; Windarsih, Anjar; Sulaiman, Ainin; Zakaria, Zalina (Taylor & Francis, 2019)
Virgin coconut oil (VCO) has emerged as functional food oil due to its capability to provide some biological activities which are beneficial to human health. This is due to the fact that some minor components like tocopherols and phenolics compounds are retained. VCO is prepared from fresh, mature kernel of the coconuts by mechanical or natural means, with or without the use of heat, but specifically without any chemical refining, bleaching and deodorizing (RBD). As a consequence, VCO has slight difference in terms of some physico-chemical properties with RBD coconut oil. Due to phenolics compounds contained, VCO exhibited several pharmacological activities including antioxidant, antiinflammatory and immunomodulatory, anti-hyperlipidemia, anticancer, antidiabetic, anti-bacterial and neuroprotective activities. VCO has commanded high price value in the fats and oils industry, hence, VCO can be target of adulteration with low priced oils. Fourier transform infrared (FTIR) spectroscopy and chromatographic techniques combined with multivariate analysis has been successfully reported for analysis of adulteration practice involving the substitution or replacement VCO with other oils. This review highlights some techniques for VCO extraction, physicochemical (characterization), biological activities and authentication analysis of VCO.